Avian Skeletal Part Representation: A Case Study from Offing 2, A Hunter‐Gatherer‐Fisher Site in the Strait of Magellan (Chile). (13th December 2013) - Lefèvre, C.; Laroulandie, V.; Bejenaru, L.; Serjeantson, D.
ABSTRACT The large midden site of Offing 2 (southern Chile) has yielded a series of human occupations dating back to 4200–2500 bp. From a very large collection of bird specimens, we sampled over 45 000 bird bones from four taxa (Diomedea sp., Procellaria sp., Phalacrocorax sp. and Sterna hirundinacea). The distributions of skeletal parts do not contradict the bone density and functional anatomy hypotheses for cormorants and terns, but the observed data for albatross and petrel are less convincing. The presence of most or all elements (except for the terns) indicates that the birds were brought back to the site as complete carcasses. The deficit of some of the long wing bones observed for albatross and petrel is remarkable and may indicate a particular removal for later use as raw material for tools or trade goods. Copyright © 2013 John Wiley & Sons, Ltd.